Healing of wounds in diabetic rats treated with Rosa rubiginosa oil - Nascimento, Isadora Azevedo Medeiros; Pinheiro Gomes, Maria Eduarda Pinheiro Gomes; Gomes Fernandes, Naíla Esther; Medeiros Azevedo, Ítalo; de Alcântara Oliveira Ramalho Borges, Rachel; Cunha Medeiros, Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
PURPOSE: This study aimed to examine if Rosa rubiginosa oil (Rro) influences the healing of skin wounds of diabetic rats. METHODS: Four groups of Wistar rats were used (6 rats/group). Group 1: skin wounds were topically treated with normal saline (NS). Group 2 had skin wounds treated with Rro for 10 days. Diabetes was induced with Streptozotocin (STZ) in groups 3 and 4. Group 3 had the wounds treated with NS. The wounds of groups 4 were treated with Rro. After anesthesia, all rats had skin excisional wounds 0.8 cm diameter. On 10th day, blood glucose and wound tissue cytokines were measured. Histometry of wounds was studied. RESULTS: Glycemia levels of 3 an 4 group rats were >250 mg%. Diabetic and non diabetic rats treated with Rro had wound tissue TNF-α, IL-1β and IL-6 expression lower than in rats receiving NS. The histological inflammatory score of Rro treated diabetic rats (19±2.7) was significantly higher than in rats treatment with NS (14±2.5). CONCLUSION: The topical treatment of skin wounds in diabetic rats with Rosa rubiginosa oil positively influenced the healing.